Mechanisms for Accessing Insoluble Fe(III) Oxide during Dissimilatory Fe(III) Reduction by Geothrix fermentans - Nevin, Kelly P. (American Society for Microbiology, 2002)
Mechanisms for Fe(III) oxide reduction were investigated in Geothrix fermentans, a dissimilatory Fe(III)-reducing microorganism found within the Fe(III) reduction zone of subsurface environments. Culture filtrates of G. fermentans stimulated the reduction of poorly crystalline Fe(III) oxide by washed cell suspensions, suggesting that G. fermentans released one or more extracellular compounds that promoted Fe(III) oxide reduction. In order to determine if G. fermentans released electron-shuttling compounds, poorly crystalline Fe(III) oxide was incorporated into microporous alginate beads, which prevented contact between G. fermentans and the Fe(III) oxide. G. fermentans reduced the Fe(III) within the beads, suggesting that one of the compounds that G. fermentans releases is an electron-shuttling compound that can transfer electrons from the cell to Fe(III) oxide that is not in contact with the organism. Analysis of culture filtrates by thin-layer chromatography suggested that the electron shuttle has characteristics similar to those of a water-soluble quinone. Analysis of filtrates by ion chromatography demonstrated that there was as much as 250 μM dissolved Fe(III) in cultures of G. fermentans growing with Fe(III) oxide as the electron acceptor, suggesting that G. fermentans released one or more compounds capable of chelating and solubilizing Fe(III). Solubilizing Fe(III) is another strategy for alleviating the need for contact between cells and Fe(III) oxide for Fe(III) reduction. This is the first demonstration of a microorganism that, in defined medium without added electron shuttles or chelators, can reduce Fe(III) derived from Fe(III) oxide without directly contacting the Fe(III) oxide. These results are in marked contrast to those with Geobacter metallireducens, which does not produce electron shuttles or Fe(III) chelators. These results demonstrate that phylogenetically distinct Fe(III)-reducing microorganisms may use significantly different strategies for Fe(III) reduction. Thus, it is important to know which Fe(III)-reducing microorganisms predominate in a given environment in order to understand the mechanisms for Fe(III) reduction in the environment of interest.